The Relationship Between Long Working Hours and Stress Responses in Junior High School Teachers: A Nationwide Survey in Japan - Matsushita, Masateru; Yamamura, Schuhei (Frontiers in Psychology, 2022)
Background: Long working hours and mental health problems among teachers are a concern in Japan. More specifically, it has been reported that junior high school teachers tend to work overtime. In this study, examined the working hours of junior high school teachers in public schools and investigated the association between overtime work and stress responses across job titles. Methods: From June to December 2018, 54,772 teachers in public junior high schools completed a web-based nationwide survey regarding occupational stress and submitted self-evaluated working hours per day of the previous month. Psychological and physical stress responses were assessed using the Brief Job Stress Questionnaire. Results: Results showed that 59.6% of the participants worked 11 hours or more per day. Additionally, the length of working hours significantly differed across job titles (χ2 (30) = 5295.8, p < 0.001, Cramér’s V = 0.14). With respect to tenured teachers, sex (female), age, taking charge of the class, number of working years in the same school, working hours of 10 to 11 hours, 11 to 12 hours, 12 to 13 hours, and 13 hours or more were significantly associated with high stress, compared to those who worked less than 9 hours per day. Moreover, for fixed-term teachers, sex (female), age, working hours of 9 to 10 hours, 10 to 11 hours, 11 to 12 hours, 12 to 13 hours, and 13 hours or more were related with more stress as compared to those who worked less than 9 hours per day. On the other hand, there was no significant relationship between long working hours and stress response among vice-principals, even though they tended to work the longest hours. Conclusion: We verified that Japanese junior high school teachers work long hours. Long working hours were associated with stress responses in both tenured and fixed-term teachers, but not in vice-principals. However, vice-principals work the longest hours among teachers, and we suggest that these long working hours may be a hidden problem that is often overlooked.